Crossing the Line : Racial Passing in Twentieth-Century U.S. Literature and Culture - Wald, Gayle, 1965- (Book collections on Project MUSE., 2000)
Examines constructions of racial identity through the exploration of passing narratives including Black Like Me and forties jazz musician Mezz Mezzrow's memoir Really the Blues.